Dissipation kinetics and dietary risk assessment of spiromesifen on major summer vegetables using good agricultural practices. (23rd February 2021) - Dubey, Jatiender Kumar; Katna, Sapna; Shandil, Deepika; Devi, Nisha; Singh, Gaganpreet; Singh, Gagandeep; Singh, Shubhra; Kaushik, Ekta; Sharma, Ajay
Abstract: Dissipation kinetics and dietary risk assessment of spiromesifen is worked out on four summer vegetables, viz. okra, chilli, capsicum and brinjal (eggplant or aubergine) during March–April 2015 at the experimental farm of the Department of Entomology, Dr. Yashwant Singh Parmar University of Horticulture and Forestry Nauni, Solan using good agricultutral practices. Two foliar applications of spiromesifen @ 144.0 g.a.i./ha each were given at 10 days interval with a knapsack sprayer with the first application at the fruit initiation stage. Sample were collected up to 15 days after pesticide application and processed using a modified QuEChERS method, which was validated by doing recovery studies having recovery range and RSD within established guidelines of SANCO. Estimation of spiromesifen residues was conducted on GC–MS. The initial deposits after spraying of spiromesifen on okra, capsicum, chilli and brinjal fruit after 2 h of treatment were 1.327, 0.727, 0.800 and 0.738 mg/kg, respectively. The residues persisted up to 7 days and further dissipated and declined below the limit of quantification of <0.025 mg/kg at 10 days after treatment in all of the crops under investigation. Dissipation of spiromesifen followed first‐order kinetics. The spiromesifen residues dissipated to half in 1.6, 1.8, 1.9 and 1.7 days with the suggested safe waiting period of 8.9, 5.2, 6.0 and 7.0 in the respective crops. The hazard quotient was <1 and theoretical maximum dietary intake was less than the maximum permissible intake, which was less than the maximum residue limit in all of the vegetable crops under investigation.